An Analysis of Project-Based Learning Teaching Module by English Teachers of Senior High Schools in Lembah Gumanti - Rizma, Annisa Elmida; Zainil, Yetti (Journal of English Language Teaching, 2024)
This study is a descriptive study aimed at investigating project-based learning teaching modules compiled by English teachers as well as their problems in compiling them in the senior high school in Lembah Gumanti on the Merdeka curriculum. A total of six English teachers at senior high school in Lembah Gumanti were chosen as the participants. Qualitative analysis was used to describe the analysis of the teaching modulus compiled by an English teacher. The data from the interview was transcribed, classified, and concluded. The results of the qualitative analysis showed that the design of the project-based learning teaching module by three English teachers in Lembah Gumanti was quite appropriate. Three teachers are able quite capable to write project-based learning teaching modules by writing their entire syntax according to their characteristics. The results of the interviews showed that the other three teachers who do not use a project-based learning module faced some problems in compiling the project-based learning teaching modules on the Merdeka curriculum, the teachers are not familiar with stages the project-based learning and have difficulty determining the project topic as well as its activities in the classroom. It was concluded that the teachers need training in designing the specialized project-based learning teaching module so that they will be better for the design of teaching module based on the Merdeka curriculum